EXPERIMENTAL APPROACHES TO IMMUNOPHARMACOTHERAPY FOR TOXIC HEPATITIS - S. Yu. Dyachkova; A. V. Turovsky (Volgograd State Medical University, Pyatigorsk Medical and Pharmaceutical Institute, 2015)
Humoral and cellular factors of natural resistance in different blood vessels for experimental CCl4-hepatitis have been studied. Sharp decrease of all factors have been detected with prevailing suppression of cellular link in lever veins and gradual increase of lysozime by 14 days which supposes the use of corresponding immunoprotectors in post-desintoxication period.